ANTI-IDIOTYPIC ANTIBODIES IN DIAGNOSIS OF OPISTHORCHIASIS - Bulashev , A.K.; Serikova , Sh.S.; Eskendirova , S.Z. (Eurasian Journal of Applied Biotechnology, 2014)
The incidence of people with Opisthorchiasis in Kazakhstan is one of the highest among the CIS countries. In the disease control system the main role is given to the early diagnosis. Effectiveness of the existing diagnostic methods for Opisthorchiasis is rather low. Nowadays diagnostic test-systems developed on the basis of ELISA have promising outlook. Most suitable antigen for serological diagnosing Opisthorchiasis is excretory-secretory antigen (ES-AG). Unfortunately, immunoassays based on the use of this antigen are not enough practical because there are great difficulties in obtaining standardized metabolite of parasite. In this regard, the great interest is the using antigen’s "internal image", i.e. anti-idiotypic antibodies (AIAT) against Fab-fragments that are specific to definite epitopes. The aim of research was to obtain antibodies to idiotypes of monoclonal antibodies (Mab) specific for Opisthorchis felineus ES-AG epitope and to determine the possibility of using anti-idiotypes as an antigen in ELISA for serological diagnosis of Opisthorchiasis. Mab 4B3D9 against helminth’s antigen have been used as immunogen for obtaining AIAT. Two hybrid strains designated as 3H10A4 and 4H10D8 producing anti-idiotypes with "internal image" of Opisthorhis felineus’ antigen were created by hybridoma technique. Anti-idiotypes produced by hybridomas belonged to IgG1 and IgM, characterized by sufficient affinity with respect to the used immunogen. As expected, in sandwich immunoassay AIAT of both hybridomas, mimicking ES-AG epitope, were recognized by antibodies of dog, infested with parasite. The results of research suggest the possibility of using anti-idiotypes of hybridomas as specific antigen in the development of immunoassays for the diagnosis of Opisthorchiasis.